Analyzing the Role of Customer-Based Brand Equity (CBBE) in Shaping Purchase Intention on Instagram: A Study in the Beauty Industry - Luthfia Wikhdatul Akhsani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the impact of Customer-Based Brand Equity (CBBE) on purchase intention in the beauty industry on Instagram. In today's competitive environment, establishing strong brand equity is essential for influencing consumer purchase decisions. A quantitative approach was employed, utilizing questionnaires completed by 399 respondents selected through purposive sampling. The data were analyzed using SmartPLS 4.0 to explore the relationships among CBBE dimensions and purchase intention. The results indicate that brand awareness and brand trust are the most significant factors in driving purchase intention, followed by brand loyalty, perceived quality, and brand association, all of which contribute positively. The model demonstrates strong explanatory power, highlighting the importance of the identified constructs in shaping purchase intention. This research underscores the importance of marketers implementing high-visibility campaigns, fostering trust through transparent communication, and maintaining consistent product quality to enhance brand equity and increase purchase intention on Instagram. Future research could apply these findings to other industries and include additional variables to deepen understanding of consumer behavior in digital contexts.